Local government financing : a case of Selayang Municipal Council - Umi Hamidaton binti Mohd Soffian Lee (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study analyzes the nature and structure of local government finance specifically of Selayang Municipal Council from 2005 until 2010. The purpose of this research is to identify major sources of income and other alternatives for local governments to increase their revenue and fiscal performance in dealing with limited financial resources. It identifies the influence of decentralization and inter-governmental relationship practices among federal government, state government and local government in determining the extent of autonomy of local governments. The data were collected through annual statistics, reports, documents, interviews and other secondary sources. This study finds that according to Local Government Act of 1976, local governments are allowed to collect their own sources of revenue from local sources within the local government jurisdiction areas. But they are also entitled to receive financial assistance in the form of grants from federal and state governments through decentralization mechanisms of service delivery and inter-governmental relationships. Local governments are expected to provide a wide range of services and fulfil their responsibilities towards their local communities effectively and efficiently with sufficient financial capabilities., But they often suffer fiscal crisis in spite of grants given such as the case in Selayang. Therefore, local governments should review their present revenue sources and their viability and seek new. possibilities and avenues in order to raise their revenues.